2018
DOI: 10.25268/bimc.invemar.2018.47.2.750
|View full text |Cite
|
Sign up to set email alerts
|

Abundancia y distribución del zooplancton superficial de la zona costera Arapito – Santa Fé, Estado Sucre, Venezuela

Abstract: The study of zooplankton in the coastal zone is fundamental to understand ecological processes. The coastal zone Arapito - Santa Fe, located in the Mochima National Park, Sucre state, Venezuela, is considered an area of great natural importance and therefore the study on zooplankton was carried upon. For this reason, the composition and community structure of zooplankton were determined in 20 stations, separated in a) coastal stations and b) away from the coast during December 2008. Samples were collected obli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…1 and 2, whose taxonomic status could not be established; 2) Ditrichocorycaeus affinis (McMurrich) is designated here as D. cf. affinis according to Márquez-Rojas et al (2014b), awaiting a detailed revision of the material available in the collection; 3) the SCA records of the genus Saphirella consist of larval stages of the family Clausidiidae (Walter & Boxshall, 2021); their taxonomic position should be clarified in the future; 4) the current position of Paracalanus pygmaeus (Claus) and Oncaea gracilis (Dana) is uncertain, so they are included in the list with reservations; 5) Due to the difficulty in establishing its affinities with other species, Pachos punctatum (Claus) is provisionally included in Cyclopoida incertae sedis (Walter & Boxshall, 2021); 6) the families Clausidiidae, Corycaeidae, Lubbockiidae, Oncaeidae and Sapphirinidae belonging to the poecilostome lineage, are included in the order Cyclopoida following Khodami et al (2017) and Walter and Boxshall (2021). org/10.22201/ib.20078706e.2023.94.4177 Species of the family Caligidae are not considered in this review, because it is a group with parasitic forms of fish that are often found in plankton samples (Ohtsuka et al, 2018).…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2, whose taxonomic status could not be established; 2) Ditrichocorycaeus affinis (McMurrich) is designated here as D. cf. affinis according to Márquez-Rojas et al (2014b), awaiting a detailed revision of the material available in the collection; 3) the SCA records of the genus Saphirella consist of larval stages of the family Clausidiidae (Walter & Boxshall, 2021); their taxonomic position should be clarified in the future; 4) the current position of Paracalanus pygmaeus (Claus) and Oncaea gracilis (Dana) is uncertain, so they are included in the list with reservations; 5) Due to the difficulty in establishing its affinities with other species, Pachos punctatum (Claus) is provisionally included in Cyclopoida incertae sedis (Walter & Boxshall, 2021); 6) the families Clausidiidae, Corycaeidae, Lubbockiidae, Oncaeidae and Sapphirinidae belonging to the poecilostome lineage, are included in the order Cyclopoida following Khodami et al (2017) and Walter and Boxshall (2021). org/10.22201/ib.20078706e.2023.94.4177 Species of the family Caligidae are not considered in this review, because it is a group with parasitic forms of fish that are often found in plankton samples (Ohtsuka et al, 2018).…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…It is recognized that 40 species are often reported, so that, as a whole, they can be considered characteristics of the ecoregion community. Corycaeidae species have been continuously reported in the literature, which includes tropical and subtropical species (Campos-Hernández & Suárez-Morales, 1994;Owre & Foyo, 1967), which are very frequent and sometimes abundant in the eastern region of Venezuela (Cervigón, 1964;Márquez-Rojas et al, 2014a, 2014b. This has been attributed to the great adaptive capacity of these copepods under the changing conditions of coastal areas (Álvarez-Cadena et al, 1998;Björnberg, 1981;Suárez, 1989) and their affinity to tropical water masses (Márquez-Rojas et al, 2014a).…”
Section: Diversity Of Pelagic Copepods In the Southern Caribbean (Sca)mentioning
confidence: 99%